Dengue virus-reactive CD8+ T cells mediate cross-protection against subsequent Zika virus challenge. Issue 1 (December 2017) - Wen, Jinsheng; Elong Ngono, Annie; Regla-Nava, Jose Angel; Kim, Kenneth; Gorman, Matthew; Diamond, Michael; Shresta, Sujan
Abstract Zika virus (ZIKV) and dengue virus (DENV) are antigenically related flaviviruses that share cross-reactivity in antibody and T cell responses, and co-circulate in increasing numbers of countries. Whether pre-existing DENV immunity can cross-protect or enhance ZIKV infection during sequential infection of the same host is unknown. Here, we show that DENV-immuneIfnar1 −/− or wild-type C57BL/6 mice infected with ZIKV have cross-reactive immunity to subsequent ZIKV infection and pathogenesis. Adoptive transfer and cell depletion studies demonstrate that DENV-immune CD8+ T cells predominantly mediate cross-protective responses to ZIKV. In contrast, passive transfer studies suggest that DENV-immune serum does not protect against ZIKV infection. Thus, CD8+ T cell immunity generated during primary DENV infection can confer protection against secondary ZIKV infection in mice. Further optimization of current DENV vaccines for T cell responses might confer cross-protection and prevent antibody-mediated enhancement of ZIKV infection. Dengue virus-specific antibody and CD8+ T cells that cross-react with Zika virus have been described. Here, the authors establish a functionally protective role for cross-reactive dengue virus-specific CD8+ T cells during challenge with Zika virus.